Breast Auto-Augmentation: A Versatile Method of Breast Rehabilitation—A Retrospective Series of 107 Procedures - Kirwan, Laurence; Wazir, Umar; Mokbel, Kefah (Archives of Plastic Surgery, 2015)
Background Breast auto-augmentation (BAA) using an inferior pedicle dermoglandular flap aims to redistribute the breast tissue in order to increase the fullness in the upper pole and enhance the central projection of the breast at the time of mastopexy in women who want to avoid implants. The procedure achieves mastopexy and an increase in breast volume.Methods Between 2003 and 2014, 107 BAA procedures were performed in 53 patients (51 bilateral, 2 unilateral and 3 reoperations) with primary or secondary ptosis of the breast associated with loss of fullness in the upper pole (n=45) or undergoing explantation combined with capsulectomy (n=8). Six patients (11.3%) had prior mastopexy and 2 (3.7%) patients had prior reduction mammoplasty. The mean patients' age was 41 years (range, 19-66 years). All patients had preoperative and postoperative photographs and careful preoperative markings. Follow-up ranged from 6 months to 9 years (mean, 6.6 months).Results The range of elevation of the nipple was from 6 to 12 cm (mean, 8 cm). The wounds healed completely with no complications in 50 (94.3%) patients. Three patients had complications including 2 (3.7%) hematomas and 1 (1.9%) partial necrosis of the nipple-areola complex. Three (5.7%) patients were dissatisfied with the level of mastopexy achieved underwent a further procedure. No patient complained of scar hypertrophy.Conclusions BAA is a versatile technique for women with small breasts associated with primary or secondary ptosis. It is also an effective technique for the salvage of breasts after capsulectomy and explantation.
Keywords: Breast; Mammaplasty; Surgical flaps